2008
DOI: 10.5650/jos.57.171
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant Toxicity of Essential Oils from Some Common Spices against Pulse Beetle, Callosobruchus chinensis (Coleoptera: Bruchidae)

Abstract: In the present study, the essential oil from seven common spices, Anethum graveolens, Cuminum cyminum, Illicium verum, Myristica fragrans, Nigella sativa, Piper nigrum and Trachyspermum ammi was isolated and its insecticidal, oviposition, egg hatching and developmental inhibitory activities were determined against pulse beetle, Callosobruchus chinensis. Essential oils were isolated by hydrodistillation method using Clevenger apparatus. These essential oils caused death of adults and larvae of Callosobruchus ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 20 publications
5
53
0
1
Order By: Relevance
“…The compounds in the seed of M. fragrans were toxic against adult female German cockroaches, Blattella germanica L. (Blattodea: Ectobiidae). Myristica fragrans essential oil was toxic to the immature stage of Callosobruchus chinensis L. (Coleoptera: Bruchidae), and Lycoriella ingenua Dufour (Diptera: Sciaridae) (Chaubey 2008;Park et al 2008). The results of this and previous studies demonstrate that M. fragrans is toxic to several insect species.…”
Section: Laboratory Experimentssupporting
confidence: 59%
“…The compounds in the seed of M. fragrans were toxic against adult female German cockroaches, Blattella germanica L. (Blattodea: Ectobiidae). Myristica fragrans essential oil was toxic to the immature stage of Callosobruchus chinensis L. (Coleoptera: Bruchidae), and Lycoriella ingenua Dufour (Diptera: Sciaridae) (Chaubey 2008;Park et al 2008). The results of this and previous studies demonstrate that M. fragrans is toxic to several insect species.…”
Section: Laboratory Experimentssupporting
confidence: 59%
“…The pharmacological actions of the seeds of Nigella sativa or its constituents that have been reported include protection against nephrotoxicity and hepatotoxicity induced by either disease or chemicals [6][7][8][9][10][11][12][13][14]. The seeds/oil have anti-inflammatory [15], analgesic [4], antipyretic [16], spasmolytic [17], bronchodialator [17], antihistaminic [18], antihypertensive [19], antitumor [20], antioxidant [18], antineoplastic [9,21,22], antifertility [23], antibacterial [24], antifungal [25], antiprotozoal [26], anthelmintic [27] and insecticidal [28] activities. Treatment of rats with the seed extract for up to 12 weeks has been reported to induce changes in the hemogram that include an increase in both the packed cell volume and hemoglobin [29] and a decrease in plasma concentrations of cholesterol, triglycerides and glucose [30].…”
Section: Review and Discussionmentioning
confidence: 99%
“…The aqueous decoctions of M. fragrans have been found to be toxic to cockroaches (Anonymous, 1995). Essential oil of M. fragrans has insecticidal activity against larvae of Lycoriella ingenua (Park et al, 2008) and Callosobruchus chinensis (Chaubey, 2008). reported that M. fragrans seed and aril i.e., nutmeg and mace are potential source of botanical molluscicides against Lymnaea acuminata.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%